Readiness Of Flood Disaster Preparedness In High Risk Area Communities In North Aceh District - Yuziani Yuziani; Cut Sidrah Nadira; Harvina Sawitri; Irfanul Aulia (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Abstract: Indonesia is a country prone to floods. Flood disasters can occur anytime and anywhere. Aceh Province has a very large disaster potential, this is influenced by geographical, geological, hydrological, and demographic conditions. One of the areas in North Aceh that is often hit by floods every year, therefore it is important for the community to have good preparedness in dealing with flood disasters. Purpose: This research is to find out the description of flood disaster preparedness in the community. Patients and methods: This study is a descriptive study with a cross-sectional approach. The sampling technique used is stratified random sampling, with a total of 98 respondents residing in the North Aceh Regency. Data collection was done by distributing questionnaires. Results: The results showed that most of the community had a level of preparedness in the good category (56.1 %), then the community in the sufficient category (25.5%), and the community with a low level of preparedness (18.4%). Conclusion: this research is most of the community has a level of preparedness to face flood disasters in high-risk areas in North Aceh Regency in the good category.